KANDUNGAN GIZI, SERAT DAN DAYA TERIMA KUKIS DENGAN PENAMBAHAN TEPUNG PISANG KEPOK DAN TEPUNG KACANG MERAH UNTUK PENGENDALIAN OBESITAS PADA DEWASA - Efendy, Carine; Farida, Eko (Jurnal Gizi dan Pangan Soedirman, 2024)
Obesity control is a significant public health challenge in Indonesia, contributing to chronic diseases like type 2 diabetes, heart disease, and hypertension. Adequate fiber intake effectively reduces obesity risk by increasing satiety and improving digestive function. This study aims to analyze the differences in nutritional content, fiber, and acceptability among three cookie formulations with the addition of Kepok banana flour (Musa paradisiaca L.) and red kidney bean flour (Phaseolus vulgaris) for adult obesity control. This experimental study used a Completely Randomized Design (CRD) involving various cookie formulations. Each formulation was tested for nutritional content, including protein, fat, carbohydrates, and fiber, as well as acceptability through organoleptic tests. Data analysis was conducted using ANOVA and Tukey's post hoc test for normally distributed and homogeneous data. For non-normally distributed data, Kruskal-Wallis and Mann-Whitney tests were used. Organoleptic tests were analyzed using the Friedman and Wilcoxon tests. The results showed significant differences among formulations in terms of nutritional content and acceptability. Based on organoleptic test results, F3 had the best acceptability. This study recommends further research with long-term clinical trials to evaluate the impact of these cookies on comprehensive obesity control.